A Systematic Review of Factors That Influence Youths Career Choices—the Role of Culture - Akosah-Twumasi, Peter; Emeto, Theophilus I.; Lindsay, Daniel; Tsey, Komla; Malau-Aduli, Bunmi S. (Frontiers in Education, 2018)
Good career planning leads to life fulfillment however; cultural heritage can conflict with youths’ personal interests. This systematic review examined existing literature on factors that influence youths’ career choices in both collectivist and individualistic cultural settings from around the globe with the aim of identifying knowledge gaps and providing direction for future research. A systematic review strategy using the Joana Briggs Institute’s format was conducted. The ERIC, PsychInfo, Scopus and Informit Platform databases were searched for articles published between January 1997 and May 2018. A total of 30 articles were included in the review, findings revealed that youth from collectivist cultures were mainly influenced by family expectations, whereby higher career congruence with parents increased career confidence and self-efficacy. Personal interest was highlighted as the major factor that influenced career choice in individualistic settings, and the youth were more independent in their career decision making. Bicultural youth who were more acculturated to their host countries were more intrinsically motivated in their career decision making. Further research is imperative to guide the understanding of parental influence and diversity, particularly for bicultural youths’ career prospects and their ability to use the resources available in their new environments to attain meaningful future career goals.